DEVELOPMENT OF TOOLS FOR PVS EVALUATION AT SUBFEDERAL/ REGIONAL LEVEL - M. A. Shibayev; A. S. Oganesyan; O. N. Petrova; A. K. Karaulov (Ветеринария сегодня)
The paper demonstrates results obtained during development of tools for performance evaluation of the veterinary services (PVS) of the Subjects of the Russian Federation. Algorithm of evaluation of the regional veterinary services was described basing on the results of their activities aimed at disease freedom assurance. Such evaluation was based on the analysis and assessment of epidemic situation. The algorithm of PVS evaluation involves subsequent stages involving assessment of epidemic situation on transboundary animal diseases, assessment of epidemic situation on economically and socially significant animal diseases, determination of actual efficacy of anti-epidemic measures, specification of retrospective category and formation of consolidated evaluation of the actual anti-epidemic activities. Four levels of effective performance are specified by one of the following retrospective categories: short-term, mid-term and long-term. An additional characteristic (retrospective review) will allow answering the question on how time-constant such achieved performance level is. Results of the veterinary service performance analysis made according to the described methods may be both part of a complex system and independent evaluation performed on the regional/subfederal level or it may be used for the country regionalization for some diseases and for risk analysis made for international trade purposes.